2016
DOI: 10.5812/atr.33335
|View full text |Cite
|
Sign up to set email alerts
|

Hemiprosthesis for Femoral Neck Fractures in the Elderly: A Retrospective Study of 319 Patients

Abstract: BackgroundIn geriatric patients with Pauwels types II and III femoral neck fractures, hemiprosthesis is the therapy of choice.ObjectivesThis study was conducted to analyze the results after cemented hemiprosthesis placement, the first year after surgery.Patients and MethodsThis retrospective study was conducted on 319 patients over 70 years with displaced femoral neck fractures treated surgically at our hospital from 2007 to 2012. All medical information was available including retrospective posthospital disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Hip hemiarthroplasty is one of the most common surgery performed for femoral neck fracture other than total hip arthroplasty. Compared to total hip arthroplasty, the procedure is relatively faster, with less bleeding and earlier weight-bearing mobilisation 5 . There are no significant differences between the advanteges of cementless and cemented stem, however a comparison study reported that there are more respiratory or cardiovascular complications and longer duration of surgery in cemented stem 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Hip hemiarthroplasty is one of the most common surgery performed for femoral neck fracture other than total hip arthroplasty. Compared to total hip arthroplasty, the procedure is relatively faster, with less bleeding and earlier weight-bearing mobilisation 5 . There are no significant differences between the advanteges of cementless and cemented stem, however a comparison study reported that there are more respiratory or cardiovascular complications and longer duration of surgery in cemented stem 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In such patients, the BHA is considered a reasonable option to regain good function [3] . It is preferred as it requires less operative time, less blood loss, technically easier procedure than THA [4] . It also has a relatively lesser dislocation rate compared to THA [5,6] …”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] It is preferred as it requires less operative time, less blood loss, technically easier procedure than THA. [ 4 ] It also has a relatively lesser dislocation rate compared to THA. [ 5 , 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…In such patients, bipolar hemiarthroplasty(BHA) is considered a reasonable option to regain good function 3 . It is preferred as it requires less operative time, less blood loss, technically easier procedure than total hip arthroplasty 4 . It also has a relatively lesser dislocation rate compared to total hip arthroplasty 5,6 .…”
Section: Introductionmentioning
confidence: 99%